Pengaruh Pengerolan Alur Pelat Heksagonal Terhadap Frekuensi Pribadinya Dalam Kondisi Bebas-Bebas - Nurazizi Aulia, Edwira; Sukanto, Sukanto; Erwanto, Erwanto (Jurnal Inovasi Teknologi Terapan, 2023)
Public interest in pick-up cars as a means of transportation for transporting goods has continued to increase lately because they are considered more flexible for transporting raw materials, workshop products and agricultural products and are capable of being operated on urban and rural roads that have different road roughness, as well as in very high traffic conditions. Plate panels that must be used in pick-up vehicles need to be designed as thin as possible but have high stiffness and natural frequency so that they are more efficient in fuel use and able to withstand vibrations that occur during driving. This study aims to determine the natural frequency that occurs in the plate panel profile for vehicle bodies resulting from the cold rolling process. The galvanized steel plates used are 0.6 and 0.8 mm thick. The natural frequency test method is used with free boundary conditions, where the conditioning plate is suspended by a rope. The natural frequency test tool used is the vibroport 80 at an existential pressure of 10 grams, with the hammer hitting the centre of the panel and the sensors being positioned at 0 and 90 degrees. Based on the test results that have been carried out, the panel specimen with a thickness of 0.8 mm obtained the highest natural frequency value of 922.5 Hz, while for a plate thickness of 0.6 mm, the highest value was only 816.25 Hz. However, the two groups of specimens with plate panel thicknesses of 0.6 and 0.8 mm because of rolling experienced an average increase in natural frequency, reaching 2.3 – 2.5 times when compared to the flat plates without the rolling process. The conclusion is that as the natural frequency value increases, the plate panel stiffness also increases.